Prognosis of patients with peritoneal metastatic colorectal cancer given systemic therapy: an analysis of individual patient data from prospective randomised trials from the Analysis and Research in Cancers of the Digestive System (ARCAD) database. Issue 12 (December 2016) - Franko, Jan; Shi, Qian; Meyers, Jeffrey P; Maughan, Timothy S; Adams, Richard A; Seymour, Matthew T; Saltz, Leonard; Punt, Cornelis J A; Koopman, Miriam; Tournigand, Christophe; Tebbutt, Niall C; Diaz-Rubio, Eduardo; et al.
Summary: Background: Patients with peritoneal metastatic colorectal cancer have reduced overall survival compared with patients with metastatic colorectal cancer without peritoneal involvement. Here we further investigated the effect of the number and location of metastases in patients receiving first-line systemic chemotherapy. Methods: We analysed individual patient data for previously untreated patients enrolled in 14 phase 3 randomised trials done between 1997 and 2008. Trials were included if protocols explicitly pre-specified and solicited for patients with peritoneal involvement in the trial data collection process or had done a formal peritoneum-focused review of individual pre-treatment scans. We used stratified multivariable Cox models to assess the prognostic associations of peritoneal metastatic colorectal cancer with overall survival and progression-free survival, adjusting for other key clinical-pathological factors (age, sex, Eastern Cooperative Oncology Group (ECOG) performance score, primary tumour location [colon vs rectum], previous treatment, and baseline BMI). The primary endpoint was difference in overall survival between populations with and without peritoneal metastases. Findings: Individual patient data were available for 10 553 patients. 9178 (87%) of 10 553 patients had non-peritoneal metastatic colorectal cancer (4385 with one site of metastasis, 4793 with two or more sites of metastasis), 194 (2%) patients had isolated peritoneal metastatic colorectal cancer, and 1181 (11%) had peritoneal metastatic colorectal cancer and other organ involvement. These groups were similar in age, ethnic origin, and use of targeted treatment. Patients with peritoneal metastatic colorectal cancer were more likely than those with non-peritoneal metastatic colorectal cancer to be women (565 [41%] of 1371 vs 3312 [36%] of 9169 patients; p=0·0003), have colon primary tumours (1116 [84%] of 1334 patients vs 5603 [66%]; p<0·0001), and have performance status of 2 (136 [10%] vs 521 [6%]; p<0·0001). We recorded a higher proportion of patients with mutated BRAF in patients with peritoneal-only (eight [18%] of 44 patients with available data) and peritoneal metastatic colorectal cancer with other sites of metastasis (34 [12%] of 289), compared with patients with non-peritoneal metastatic colorectal cancer (194 [9%] of 2230; p=0·028 comparing the three groups). Overall survival (adjusted HR 0·75, 95% CI 0·63–0·91; p=0·003) was better in patients with isolated non-peritoneal sites than in those with isolated peritoneal metastatic colorectal cancer. Overall survival of patients with two of more non-peritoneal sites of metastasis (adjusted HR 1·04, 95% CI 0·86–1·25, p=0.69) and those with peritoneal metastatic colorectal cancer plus one other site of metastasis (adjusted HR 1·10, 95% CI 0·89–1·37, p=0·37) was similar to those with isolated peritoneal metastases. Compared with patients with isolated peritoneal metastases, those with peritoneal metastases and two or more additional sites of metastasis had the shortest survival (adjusted HR 1·40; CI 1·14–1·71; p=0·0011). Interpretation: Patients with peritoneal metastatic colorectal cancer have significantly shorter overall survival than those with other isolated sites of metastases. In patients with several sites of metastasis, poor survival is a function of both increased number of metastatic sites and peritoneal involvement. The pattern of metastasis and in particular, peritoneal involvement, results in prognostic heterogeneity of metastatic colorectal cancer. Funding: None.